Pengaruh Kemudahan, Kepercayaan dan Persepsi Risiko terhadap Keputusan Pembelian menggunakan Pembayaran Shopee Paylater pada Mahasiswa Kota Batam - Habiballah, Ananda; Rustam, Triana Ananda (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study was designed to explore the influence of convenience, level of trust, and risk perception on purchasing decisions through the use of Shopee PayLater facilities among active students in Batam City. This study uses a quantitative descriptive approach. The target population includes students in Batam City who have used the Shopee PayLater service, although the exact number is unknown. The sampling process applies the Jacob Cohen formula with a purposive sampling method, resulting in 204 respondents. Data processing includes data quality testing, classical assumption testing, influence analysis, and hypothesis testing. The results of multiple linear regression show that the convenience variable has an influence of 30.8% on purchasing decisions, while the level of trust contributes 19.0%, and risk perception 30.4%. The coefficient of determination (R²) analysis states that 70.8% of the variation in purchasing decisions is explained by convenience, trust, and risk perception. The t-test and F-test support this finding, indicating that the three variables significantly and positively influence purchasing decisions, both individually and together.